A polêmica em torno do livro didático “Por uma Vida Melhor” : (des)construindo sentidos - Pádua, Dinaura Batista de (2014)
This paper aims at developing a dialogical analysis of the discourses which emerged in the media sphere because of the controversy of the textbook "Por uma vida melhor", which had its beginning in May 2011, having been featured on various radio and TV stations, plus magazines, newspapers, blogs and official websites. To this end, we seek grounding in the theoretical-methodological basis present in the theoretical constructs of the Bakhtin Circle, from the dialogical conception of language, given that the reading of these texts revealed an intense dialogue, in which, in Bakhtin's view, a text "replied the other", a text was "response" of another, in an unbroken dialogical chain. The analysis of the selected corpus is based on the sociological method to the study of language, through which we place the sphere of production, circulation and reception of these discourses, describe the characteristics and regularities of the genre and highlight linguistic and enunciative strategies used to produce meanings in these social relations, indicating to ethical and political valuation. Realizing the language as a privileged site of interaction between subjects, from the analysis undertaken, we describe and explain the discursive practices that have established in the media sphere because of the controversy, revealing the voices in these enunciative relations, identifying their ideological positions in face of the event. The results of our analysis indicate discursive marks of an endless dialogue around the controversy, whereby social voices from different spheres (political, academic, scientific, religious, and above all, common sense) valuate through word. These voices dialogue not only on the book itself, but about their attitudes towards language and its variations, the first language teaching, the linguistic science, and the teacher/researcher of Portuguese Language and, also, about the book's author, Professor Heloisa Ramos, the federal government, the Workers' Party, the Ministry of Education and the Minister Fernando Haddad. These dialogues are evidenced by movements of approach or distancing from the speech of the other and the calling of other voices. Among the strategies used by the enunciators in the enunciative formations analyzed, we highlighted: the use of terms present in previous speeches, in order to resume or give new meaning to what was said; use of punctuation, quotes, bolds, italics, parentheses; use of direct or indirect speech; use of the verb in the passive voice; changes of tense (conditional tense) to cast doubt on an event, a social fact; use of adjectives and nouns to characterize the other of whom one speaks; use of memories, as the elementary school teacher, besides renowned writers of our classical literature, as arguments of authority, in order to gain the credibility of readers. These results point to the relevance of the study of discursive practices constructed in the media sphere, demonstrating the heuristic possibilities of Bakhtinian theoretical constructs, especially the dialogical conception of language.